The Influence Of Division Of Labor And Supervision On Employee Work Effectiveness At PT. Light Riau Mandiri - Nidyawati Nidyawati; Darwin Kesuma; Melia Andayani; Vemy Fytaloka (UNIVED Press, 2024)
This study aims to determine the effect of division of labor and supervision on employee work effectiveness at PT Cahaya Riau Mandiri. The sample in this study amounted to 88 respondents who were distributed to employees of PT Cahaya Riau Mandiri. The data analysis method used is quantitative analysis using Data Quality Test (Validity Test and Reliability Test), Inferential Statistical Test (Multiple Linear Regression, Correlation Coefficient, Coefficient of Determination, t test, and F test). The results of the analysis obtained Division of Labor has a positive and significant effect on Employee Work Effectiveness at PT Cahaya Riau Mandiri, this can be seen from the t value (8.037) > t table (1.989). And Supervision has a positive and significant effect on Employee Work Effectiveness at PT. Cahaya Riau Mandiri, this can be seen from the value of t count (2.171) > t-table (1.989). As well as Division of Labor and Supervision have a positive and significant effect on Employee Work Effectiveness at PT. Cahaya Riau Mandiri, this can be seen from the value of F count (59.553) > F table (3.953) and the significance value < the significance level (α) 0.05 (0.000 < 0.05).